An explicit–implicit combined model for predicting residual strength of composite cylinders subjected to low velocity impact. (1st September 2020) - Liao, Binbin; Jia, Liyong; Zhou, Jianwu; Lei, Hongshuai; Gao, Ruxin; Lin, Yuan; Fang, Daining
Abstract: Composite structures are susceptible for low velocity impact, which leads to the reduction of the residual strength. In present paper, an explicit–implicit combined model based on stress-based failure and damage evolution laws is introduced for predicting residual strengths of composite cylinders subjected to low-velocity impact. The whole-process of damage evolution in composites can be explored by using direct damage state at the end of impact for residual strength analysis instead of traditional equivalent method. Then the proposed model is implemented by user-defined subroutines and Python scripting language in ABAQUS. VUAMT and UMAT subroutines are used for explicit impact analysis and implicit residual strength analysis, and Python scripting language is applied for damage data linking between the explicit–implicit modules. Relatively consistent experimental data and numerical results for the low velocity impact behaviors and residual tensile strength in T300/YH69 laminates validate the current model. Finally, residual strengths of composite cylinders after impact consisting of five impact energies are numerically explored. The residual burst pressure after impact and damage mechanism withstanding internal pressure of cylinders are predicted. The fiber damage caused by impact loading at hoop layers is determined as the dominant influencing mechanism affecting the residual strength of composite cylinders.